Increasing habitat suitability in the United States for the tick that transmits Lyme disease: a remote sensing approach. - Estrada-Peña, Agustín (2002)
The warnings about the spread of (italic)Ixodes scapularis(/italic), one of the vectors of Lyme disease, into the United States are based on reports about regional distribution and increasing local abundance. In a modeling approach, I used the recorded, current distribution of this tick and remotely sensed bioclimatic factors over the United States to establish the changes of habitat for this tick since 1982 and to detect the areas with factors adequate to support tick colonization. Results indicate the geographic expansion of areas with adequate habitat suitability in the period 1982-2000. A discriminant analysis of counties with different degrees of habitat suitability shows that the increase in winter temperatures and in vegetation vitality (as a direct consequence of higher rainfall) is key to habitat switch from unsuitable to suitable.